Kinetics of copper passivation and pitting corrosion in Na2SO4 containing dilute NaOH aqueous solution - Souto, Ricardo M. (1994)
The electrochemical behaviour of Cu in alkaline solutions containing Na2SO4 was studied using potentiodynamic and potentiostatic techniques complemented by scanning electron microscopy. The presence of Na2SO4 enhances Cu electrodissolution through the passive layer and decreases the breakdown potential. There is a critical OH-/sulphate concentration ratio for the onset of localized corrosion. The competitive interaction between OH- and sulphate ions at the passive layer can explain the experimental data. Pit initiation fits the point defect model for passivity breakdown. Pit growth involves a number of current contributions which can be distinguished through the analysis of current transients at constant potential by using nucleation and growth models.